Questionable Efficacy of Therapeutic Antibodies in the Treatment of Anthrax - Tournier, Jean-Nicolas; Rougeaux, Clémence; Biot, Fabrice V.; Goossens, Pierre L. (mSphere, 2019)
Inhalational anthrax caused by Bacillus anthracis , a spore-forming Gram-positive bacterium, is a highly lethal infection. Antibodies targeting the protective antigen (PA) binding component of the toxins have recently been authorized as an adjunct to antibiotics, although no conclusive evidence demonstrates that anthrax antitoxin therapy has any significant benefit. We discuss here the rational basis of anti-PA development regarding the pathogenesis of the disease. Inhalational anthrax caused by Bacillus anthracis , a spore-forming Gram-positive bacterium, is a highly lethal infection. Antibodies targeting the protective antigen (PA) binding component of the toxins have recently been authorized as an adjunct to antibiotics, although no conclusive evidence demonstrates that anthrax antitoxin therapy has any significant benefit. We discuss here the rational basis of anti-PA development regarding the pathogenesis of the disease. We argue that inductive reasoning may induce therapeutic bias. We identified anthrax animal model analysis as another bias. Further studies are needed to assess the benefit of anti-PA antibodies in the treatment of inhalational anthrax, while a clearer consensus should be established around what evidence should be proven in an anthrax model.